Designing a Comfortable Educational Environment - Borisovna Bakhtigulova, Lyudmila; Victorovich Matveev, Oleg; Vyacheslavovna Luchina, Elena; Aleksandrovna Mamaeva, Yulia; Aleksandrovna Suchilina, Anna; Vyacheslavovna Vizaulina, Victoria (International Journal of Engineering and Technology, 2018)
Introduction. The problem of maintaining the physical health of teachers in educational organizations is discussed in the article in the context of professional â€œburnoutâ€ and conflict prevention. Research methodology. When studying the content and essence of a comfortable educational environment, we were interested in the works that provided for an understanding of the nature of human interaction and reflected the interdependence and communication style of people in direct contact with each other. Research results. The most important factor of external and internal order, determining the content, direction and intensity of work activity, has always been a special atmosphere in the team, which in scientific and social discourse was defined by various terms such as: â€œmicroclimateâ€, â€œmoral and psychological microclimateâ€, â€œsociological microclimateâ€, â€œcomfortable educational environmentâ€. Discussion. Designing refers to the category of innovative creative activity, since it primarily involves a purposeful transformation of reality, the need for which arises whenever there is an awareness of the necessity to move to a prognostic model of an educational or upbringing system. The main purpose of such â€œeducational changesâ€ consists in the possibility for a person himself/herself to learn and self-change during life, to apply knowledge in solving professional tasks. Conclusion. The term â€œcomfortable educational environment" is used to denote a special atmosphere in the team that determines the content, direction and intensity of work activity and manifests itself in such group effects as team membersâ€™ mood and opinion, individual well-being, assessment of the personâ€™s living and working conditions in the team. This special atmosphere is regarded on the whole as a result of peopleâ€™s joint activity, their interpersonal interaction. Â Â